Giant cell granulomatous reaction during treatment of cystic acne with isotretinoin. - Milano, A; Bonifazi, E. (European Journal of Pediatric Dermatology, 2006)
A rare side effect of treatment with oral isotretinoin in patients with acne is a reaction characterized by skin fragility, ulceration and excessive granulation tissue, which is reminiscent of pyogenic granuloma. This reaction was attributed to the inhibitory activity of isotretinoin on desmosomes and collagenase and to its promoting activity on the vessel proliferation in the reticular dermis (2). However, the reaction was also observed during topical isotretinoin treatment (4) and even in patients with acne not treated with isotretinoin (3). The histological examination of the granulomatous tissue shows intermediate findings between pyogenic granuloma and granulation tissue. However, a giant cell infiltrate, as in our case, has been already reported (2). The reaction is sometimes so severe to lead to withdraw the treatment with isotretinoin. In our case the good therapeutical result of the topical treatment allowed us to continue isotretinoin, the latter being essential to cure the severe cystic acne of our patient.